Distributional consequences of remittances: Evidence from sixty-five developing countries - Muhammad Tariq Majeed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
This paper investigates the distributional consequences of international remittances using a panel data set from sixty five developing economies from 1970 to 2015. It focuses on complementarity between financial development and remittances in determining the inequality-impact of remittances using instrumental variables techniques of panel data for empirical analysis. The study finds out that inequality-effect of remittances differs between developing economies depending upon the strength of financial sector. International remittances help to the poor by reducing inequality in developing countries where financial markets are comparatively developed. However, the inequality-effect of remittances turns out to be adverse in developing economies where financial markets are underdeveloped. This effect arises because the strength of financial sector and remittances has a complimentary role in determining inequality-effect of remittances. The empirical findings of the study are robust to different specifications, econometrics techniques, additional control variables and sub-samples. This research paper contributes into the literature on inequality and remittances by highlighting the heterogeneity of developing economies in shaping the distributional effects of international remittances. It is first study of its kind, to my knowledge, that provides an empirical analysis of complementarity between financial development and remittances in shaping the inequality-effect of remittances. The main message of this research is that the strength of financial sector in remittances receiving economies is critical in determining the inequality impacts of remittances. Therefore, the governments of developing economies need to improve their financial sectors to take the maximum advantages of international remittances.
Keywords: 330; income inequality; remittances; financial sector development; developing economies